Assessment of the level of living of the population in Tambov region - Natalia V. Cheremisina; Elena V. Veiss (Статистика и экономика)
Purpose of the study. To assess the standard of living of the population of the Tambov region through statistical methods.Materials and methods. The study used the methods of analysis of the composition and structure, the calculation of absolute and relative indicators of dynamics, average values, comparative analysis, graphical method of analysis, as well as the general theoretical method of analysis of Russian and foreign literary sources. The main information sources for the study were the data from the official website of the Federal State Statistics Service, its territorial office in the Tambov region, as well as the data from the Unified Interdepartmental Statistical Information System. In addition, the works of such authors as R. Zhukov, M. Malkina, N. Zotkina, S. Ignatova, E. Sadovaya, V. Sautkina and others were analyzed.Results. The main results of the study include the following:– Over 6 years (from 2012 to 2017) in the Tambov region, the largest share of the population, namely 23.0% in 2012 and 27.1% in 2017, had an average per capita cash income of 15 to 25 thousand rubles; – In 2012, the average per capita income of a resident of the studied region was most often met for 16,381.5 rubles (fashion value), and in 2017 – 18,561.0 rubles;– In the Tambov region from 2012 to 2017, the average absolute deviation of the studied indicator from the average in Russia is 5434.1 rubles;– The purchasing power of money incomes of the population has decreased for almost all food and non-food products; – The main sources of monetary incomes of the population of the Tambov region in 2017 are the wages of employees and receipts from social benefits (their share in the income structure is more than 20%);– The structure of the budget expenditures of the population of the Tambov region in 2017 is as follows: the purchase of goods and payment for services amounted to 77.5; mandatory payments and fees - 7.7%; real estate purchase - 1.9%; growth of financial assets - 12.9%;– The size of the average per capita monetary income of the population is inversely related to the unemployment rate of the region.Conclusion. In general, summing up the study, we can draw the following conclusion. For a number of indicators characterizing the standard of living of the population of the Tambov region, there is a positive trend, for example, an increase in the average per capita cash income of the population. Another positive trend was found: an inverse relationship between the unemployment rate and average per capita income. However, despite this, in our region it is lower than the average in Russia. Half of the population has incomes less than 17,730 rubles, and the most common income is in the amount of 18,561 rubles, which is significantly lower than the average for the Tambov region.